Manajemen Pendidikan Islam dalam Perspektif Hadist - Windayani Windayani; Ilyas Husti; Nurhadi Nurhadi (At-Tajdid : Journal of Islamic Studies, 2022)
Education management has a strategic role for educational development. In other words, Islamic education management is the art and science of managing Islamic educational resources to achieve educational goals effectively and efficiently. When talking about management, of course it cannot be separated from the existing components, namely planning, organization, implementation and control. In the Islamic paradigm, experts conclude that the concept of management of Islamic education from the point of view of al-Hadith as flexibility, efficiency, effectiveness, openness, cooperation and participation for the world of education. The purpose of Islamic education management is that all resources, equipment or facilities in an organization can be relocated in such a way as to avoid loss of time, energy, material and money, in order to achieve predetermined organizational goals.